Photoredox reactions of environmental chromium - Piotr Mytych; Paweł Cieśla; Zofia Stasicka (International Journal of Photoenergy)
The role of direct photochemical reactions of Cr(VI) and Cr(III) species in the environmental degradation of organic matter was investigated by means of Cr(VI)/alcohol and Cr(III)/EDTA model systems under conditions mimicking the environmental ones. Photoreduction of Cr(VI) proceeds through reductive quenching of chromate(VI) excited within UV-A by an alcohol molecule. Although HCrO4− is more susceptible to the quenching than the CrO42− ion, and oxygen favours the reverse reaction, the reduction can be easy noticeable at air-saturated natural waters. Photoredox behaviour of [crEDTA(L)]n- is more complex: it is initiated also by photoreduction, Cr(III) hv→ Cr(II), which at alkaline medium and a large excess of O2 over Cr(II) is followed by the Cr(II) → Cr(VI) oxidation. Both the photoreductions are accompanied by oxidation of organic matter. Due to the substitutional lability of the [crEDTA(L)]n- complexes the conditions can be adjusted under which the Cr(VI)/Cr(III) forms are able to mediate the O2 oxidation of organic matter in the environmental photocatalytic cycle.